2014
DOI: 10.1186/1471-2474-15-425
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 enhances the expression of osteoarthritis-associated genes in synovial fibroblasts in culture

Abstract: BackgroundRecent work has shown that the gap junction protein connexin43 (Cx43) is upregulated in cells of the joint during osteoarthritis (OA). Here we examined if the OA-associated increase in Cx43 expression impacts the function of synovial fibroblasts by contributing to the production of catabolic and inflammatory factors that exacerbate joint destruction in arthritic disease.MethodsUsing rabbit and human synovial fibroblast cell lines, we examined the effects of Cx43 overexpression and Cx43 siRNA-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 54 publications
(64 reference statements)
1
26
0
Order By: Relevance
“…The activation of ERK1/2 and small mothers against decapentaplegic homolog (Smad) signaling pathways leads to increased TGF-β1 -induced Cx43 expression, which is required for the differentiation of trophoblast cells [14]. Cx43 is also up-regulated in cells in the joints of patients with osteoarthritis, and targeting Cx43 expression may be a feasible therapeutic strategy to alleviate the inflammatory and catabolic environment of the joint during osteoarthritis [15]. Additionally, BMPs are also known for their importance in the differentiation of osteoblastic lineage and osteogenesis [16].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of ERK1/2 and small mothers against decapentaplegic homolog (Smad) signaling pathways leads to increased TGF-β1 -induced Cx43 expression, which is required for the differentiation of trophoblast cells [14]. Cx43 is also up-regulated in cells in the joints of patients with osteoarthritis, and targeting Cx43 expression may be a feasible therapeutic strategy to alleviate the inflammatory and catabolic environment of the joint during osteoarthritis [15]. Additionally, BMPs are also known for their importance in the differentiation of osteoblastic lineage and osteogenesis [16].…”
Section: Introductionmentioning
confidence: 99%
“…The supernatant was used for protein expression analysis by western blotting. For BMSCs, cells were lysed in modified RIPA, as described (Gupta et al, 2014).…”
Section: Protein Extractsmentioning
confidence: 99%
“…Gupta et al 19 reported that increasing Cx43 expression enhanced the gene expression of IL-6, and knockdown of Cx43 decreased expression of IL-6 in osteoarthritis synovium. Therefore, we expected that the expression of Cx43 of synovial tissue was inhibited by tocilizumab which could decrease the expression of IL-6 in synovium.…”
Section: Discussionmentioning
confidence: 99%